Design and Construction of Tempeh Slicer - Fauzan Luhfi; Achwil Putra Munir; Sulastri Panggabean (Universitas Sumatera Utara, 2016)
Slicing is reduction of the size of the foodstuffs into slices with a certain degree of thickness to be more easily processed into other products, one of them is into chips. This research was aimed to design, create, test and analyze the economic value tempeh slicer. Parameters observed were the effective capacity of the tool, the percentage of damaged materials, and economic analysis. Based on this research, it was summarized that the effective capacity of the equipment was 85.26 kg/hour and the damaged material’s percentage was 15.3%. Economic analysis was as follows: basic costs for the first to the fifth year ware Rp. 128.416 / kg, Rp. 128.635 / kg, Rp. 128.870 / kg, Rp. 129.123 / kg and Rp. 129.395 / kg respectively. Break even point was 236,66 kg / year. Net present value was Rp. 1.270.819.564,93. Internal rate of return was 52,68%. Keywords: tempeh, knife, slicing, equipment